Chemical states of surface oxygen during CO oxidation on Pt(1 1 0) surface revealed by ambient pressure XPS. (20th October 2017) - Yu, Youngseok; Koh, Yoobin Esther; Lim, Hojoon; Jeong, Beomgyun; Isegawa, Kazuhisa; Kim, Daehyun; Ueda, Kohei; Kondoh, Hiroshi; Mase, Kazuhiko; Crumlin, Ethan J; Ross, Philip N; Gallet, Jean-Jacques; et al.
Abstract: The study of CO oxidation on Pt(1 1 0) surface is revisited using ambient pressure x-ray photoemission spectroscopy. When the surface temperature reaches the activation temperature for CO oxidation under elevated pressure conditions, both the α -phase of PtO2 oxide and chemisorbed oxygen are formed simultaneously on the surface. Due to the exothermic nature of CO oxidation, the temperature of the Pt surface increases as CO oxidation takes place. As the CO/O2 ratio increases, the production of CO2 increases continuously and the surface temperature also increases. Interestingly, within the diffusion limited regions, the amount of surface oxide changes little while the chemisorbed oxygen is reduced.